POLITIK HUKUM PENERAPAN OVERSEAS CITIZENSHIP OF INDIA (OCI) DALAM SISTEM KETATANEGARAAN INDONESIA - Mahardika, Ahmad Gelora (Legality : Jurnal Ilmiah Hukum, 2019)
The idea of implementing a dual citizenship system in Indonesia which was initiated by the Indonesian Diaspora was directed towards imitating the Overseas Citizenship Of India (OCI)Â  concept in India. The concept is considered a middle way between the demands of the Indian Diaspora and the reluctance of the Indian Government to amend the constitution regarding the principle of single citizenship. Indonesia also currently applies a single citizenship principle even though it is not regulated in the constitution. The idea of an Indonesian diaspora to emulate the OCI concept in India looks very rational, except that the problem is the extent to which the concept is applicable in the Indonesian constitutional system. What rules must be changed and which provisions must adjust. Implications of the application of OCI can be the same as dual citizenship, because the theory used is a residual theory where, apart from the prescribed restrictions, OCI card holders must be considered equal to Indonesian citizens. This concept has the potential to create legal complexity if there is a legal difference between Indonesia and other countries.